BILLFISH CATCHES FROM OCEANIC RECREATIONAL FISHING IN THE ROYAL CHARLOTTE BANK, BAHIA, BRAZIL - Camila PRIMITIVO; Alexandre SCHIAVETTI; Kátia Meirelles Felizola FREIRE (Boletim do Instituto de Pesca)
The aim of this study was to analyze the oceanic recreational fishing in the Royal Charlotte Bank, state of Bahia, Brazil. Only data from an oceanic recreational fishing operator based in the municipality of Canavieiras, southern Bahia, were used, from 2012 to 2017. Overall, 103 fish specimens were caught and released, during this period, belonging to the following species: Makaira nigricans, Kajikia albida, and Istiophorus platypterus. Fishery operations occurred from October to March, with the highest catch in number in December (56.3%). The largest annual catch was recorded in 2013, with 39 individuals. The catch per unit effort ranged from 1.0 to 1.4 fishes per trip, with the highest value in December. Even though data presented here are partial, they can help to establish a strategic scenario for the fishing sector in Bahia, along with data from other fishing sectors (artisanal, industrial, subsistence and scientific).